PENGARUH PEMBERIAN KOMPRES JAHE TERHADAP PENURUNAN INTENSITAS NYERI PUNGGUNG BAWAH PADA IBU HAMIL TRIMESTER III DI KLINIK BIDAN WINDA ASTUTI AM.KEB - Siregar, G.F Gustina; Purba, Tetty Junita; Wahyuni, Eka Sri; Putri, Ananda Azhari (JURNAL ILMIAH DHDT - KEBIDANAN, 2025)
The physiological process of pregnancy occurs in women as a result of the fertilization of male and female sex cells. Pregnancy discomfort can occur at any time during the first, second, or third trimester of pregnancy. Back pain is a common discomfort that occurs in the first trimester of pregnancy. The increasing burden of the uterus, lifting heavy loads, bending over for long periods, and walking restlessly are the causes of these changes. In terms of non-pharmacological back pain relief, ginger compresses are one effective method. This study used a two-group pre-test-post-test research design using a quasi-experimental methodology. This study was conducted at the Winda Astuti Am.Keb Marelan V Pasar II Barat Midwife Clinic, Medan Marelan District in 2024. The number of research samples was 40 people. The Wilcoxon test was used in this study. At the Winda Astuti Am. Midwife Clinic. Marelan V Pasar II Barat Village, Medan Marelan District in 2024, a study was conducted on the effect of giving ginger compresses on reducing the intensity of back pain in pregnant women in the third trimester with a value of 0.000 <0.05, which means Ha is accepted and Ho is rejected.